Predicting sports results with artificial intelligence – a proposal framework for soccer games - Fialho, Gabriel Pinto (2020)
As the sports betting industry and technology have grown on a large scale, predicting the outcome of a sports match using technologies approach is now crucial. In fact, humans have a certain limitation when processing a large set of information. However, Artificial Intelligence techniques can overcome this issue. Furthermore, sports have a great amount of data to consider, thus, it is a great example of AI problem. A review of some research using different Artificial Intelligence techniques to predict a sport outcome is presented in this article. Different types of sports such as football, soccer, javelin throw, basketball, and horse race were analyzed, and showed distinct approaches to predict results. Finally, a framework to develop a system to predict the outcome of a soccer game based on AI is proposed, considering the present research review.